Efectos del proceso de fermentación y secado del grano sobre el rendimiento y calidad del cacao - Mora Posligua, Presly Carol (2016)
SUMMARY This research was conducted in the cocoa plantation and `` Nacional' CCN - 51', Hacienda "Bella Sombra" belonging to Mr. Gil Mora García, located in the Montalvo way - Complex La Estrella, Canton Montalvo, Province Rivers, in order to: 1) Determine the appropriate period of fermentation to improve the quality of cocoa; 2) identify the best method of drying cocoa was rented aimed at improving the taste and aroma of cocoa; and 3) determine which of the cocoa, have improved flavor and aroma qualities. Treatments were made by combinations fermentation period and drying methods, as follows: (T1), (T2), (T3) had a fermentation period of 2,3 and 4 days and dried in the drying area; (T4), (T5) and (T6) fermentation period of 2.3 to 4 days and dried in dryer; giving a total of six treatments. Experimental design "randomized complete blocks" was used in three repetitions, both cocoa and `` Nacional' CCN - 51'. The analysis of variance was performed separately for each cocoa. The variables were evaluated: percentage of chalky grains, grain percentages moldy grain percentages violet; percentages of grain with good fermentation; percentage of slightly fermented grain; and total percentage of fermented beans. Also the organoleptic analysis of samples was conducted both cocoa studied. All variables were subjected to analysis of variance and statistical significance test of Tukey was used at 95% probability for comparisons of the treatment means. Statistical analysis and interpretation of experimental results, it was concluded: 1. The percentage of chalky grain and grain mold decreased with days of fermentation; while it is increasing the percentage of grain violet in cocoa `Nacional'. 2. The total percentage of cocoa beans fermented `Nacional', was obtained with treatment (T2) three days of fermentation and drying clothes line, with an average of 69.45%. 3. `Trinidadian cacao CCN - 51', the lowest percentage of chalky grain was 7.08% lower when the fermentation period was 4 days and drying clothes line. 4. The highest total percentage of fermented grains was obtained with treatment (T1) two days of fermentation and dried tendal, with 70.48%. 5. The values of acidity, astringency and bitterness were higher when the dryer dried in both cocoa. It was recommended: 1. Dewatering method should be done within tendal to achieve a higher total percentage of fermented beans. 2. The fermentation process must be 3 days in cocoa `Nacional' and more than 4 days in cocoa` CCN - 51'. 3. Continue research in other ecological zones.